Innovative Approaches to Staff Motivation Based on ESG Business Principles and Intellectualisation: International Experience - Maslak, Olga; Pochtovyuk, Andrii; Yakovenko, Yaroslava; Maslak, Mariya; Grishko, Natalya; Marchenko, Vitalii (Innowacyjne podejścia do motywacji pracowników w oparciu o zasady ESG biznesowe i intelektualizację: międzynarodowe doświadczenie, 2022)
The theoretical and methodological principles of the use of innovative approaches to personnel motivation are determined, and the methodology of personnel motivation management based on ESG is considered using the example of the USA, Japan, and Europe. Western European companies are characterised by three models of labour incentives: non-bonus (work incentive functions are performed by wages); bonus, which includes payments in the amount related to the size of the company’s income or profit; bonus, which provides for payments determined by individual work results. The necessity of using modern work motivation systems based on the accounting of motivational effects, the application of work performance assessment criteria, the forecast of the work behaviour of personnel regarding changes in the work motivation system in the organization, and the monitoring of important deviations from the given form of work behaviour, was proven. Areas of personnel productivity were investigated based on an adapted algorithm of the principal components’ method, which made it possible to compare the positions of international companies relative to their competitors and quantify their achievements in personnel motivation. This made it possible to form the general components of a modern universal approach to the motivation of highly productive work.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 45-58
Keywords: innovation; intellectualisation; motivation; ESG principles; work behaviour; innowacje; intelektualizacja; motywacja; zasady ESG; zachowania w pracy